2014
DOI: 10.1071/rd12243
|View full text |Cite
|
Sign up to set email alerts
|

Production of viable cloned miniature pigs by aggregation of handmade cloned embryos at the 4-cell stage

Abstract: The aim of the present study was to improve the quality of handmade cloned porcine embryos by multiple embryo aggregations. Embryos derived from aggregation of three cloned embryos (3×) had a better blastocyst rate than cloned control (1×) embryos (73.6% vs 35.1%, respectively; P<0.05), but did not differ from those produced by aggregation of two cloned embryos (2×; 63.0%). Total cell numbers differed among treatments (P<0.05), with the greatest cell numbers (126) in the 3× group and the lowest (55) in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 58 publications
4
25
1
Order By: Relevance
“…Balbach et al (2010) reported that aggregation of mouse cloned embryos normalized the levels of CDX2 and this effect was attributed to higher cell numbers. In contrast to our findings, embryo aggregation in miniature pigs enhanced the expression of OCT4 and CDX2 (Siriboon et al 2014).…”
Section: Scnt and Embryo Aggregation In Felidscontrasting
confidence: 56%
See 1 more Smart Citation
“…Balbach et al (2010) reported that aggregation of mouse cloned embryos normalized the levels of CDX2 and this effect was attributed to higher cell numbers. In contrast to our findings, embryo aggregation in miniature pigs enhanced the expression of OCT4 and CDX2 (Siriboon et al 2014).…”
Section: Scnt and Embryo Aggregation In Felidscontrasting
confidence: 56%
“…This mixture would compensate for epigenetic problems of one individual embryo. This approach, which is called embryo aggregation, results in higher blastocyst cell numbers, normalization of pluripotent gene expression and higher in vivo development in the mouse and miniature pigs (Boiani et al 2003, Balbach et al 2010, Siriboon et al 2014). Moreover, rates of blastocyst production improved for bovine and equine aggregated embryos as also did blastocyst cell numbers and pregnancy rates (Pedersen et al 2005, Zhou et al 2008, Ribeiro Ede et al 2009, Gambini et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that for a successful cloning, the pattern of epigenetic modifications in the donor cells must be remodeled to be similar to the pattern present in the fertilized embryos [35].As a result, we performed embryo aggregation and obtained a significant increase in in vitro embryo development and cell number, 20% cleavage and a three-fold increase in blastocyst rate. Similar observations were also reported following embryo aggregation in domestic animals such as the pig following aggregation of 2 cells [33], or of 4 cells [11,14,36,37] and in the bovine [17], the horse [8,9] and the feline [10]. Increased cleavage, development rates and cell number proved that the medium used was adequate for normal development.…”
Section: Cloned 1x Blastocystsupporting
confidence: 67%
“…Embryo aggregation consists of placing more than one zona free embryos in the same well; some of the reported benefits in mammals are: improvement in embryo development in pig [6], equine [8,9], feline [10] and mouse [11], increasing the density of cells in the inner cell mass on cattle [12], blastocyst diameter in equine and in bovine [8,13], reduction in apoptosis in bovine and pigs [13,14,15], normalization of gene expression in bovine [15]and in some cases, it has also improved in vivo embryo development and early pregnancy rates in mouse [11], equine [8] and in cattle [13,16,17]. As a single clone may have epigenetic defects [15], embryo aggregation could compensate the reprogramming deficiencies through the interactions between blastomeres [11] or by paracrine pathways [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lanes 1, 3, 5, 7, 9, 11, 13, 15, 17, 19, and 21: the EGFP gene was detected in the ear genomic DNA from piglets 2453, 2455, 2457, 2459, 2460, 2461, 2462, and 2463; EGFP expressing cells; tdTomato-transfected cells; and ddH 2 O (negative control), respectively; lanes 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, and 22: the tdTomato gene was detected in the ear genomic DNA from piglets 2453, 2455, 2457, 2459, 2460, 2461, 2462, and 2463; EGFP-expressing cells; tdTomato-transfected cells; and ddH 2 O (negative control), respectively. (C)The EGFP gene and the tdTomato gene were amplified from genomic DNA from different tissues of Rature.Lanes 1,3,5,7,9,11,13,15,17,…”
mentioning
confidence: 99%